Industry perspectives on digital out-of-home advertising in South Africa - Thérèse Roux (Communicare)
Digital out-of-home (DOOH) advertising, the so-called “new kid on the block”, is not exactly a child any more. DOOH advertising has become one of the most promising marketing communication platforms. Remarkable growth rates are projected in both developed and emerging markets. Studies on DOOH advertising are generally limited to a few leading authors from developed markets. However, practitioners’ perceptions and practices remain unknown. Understanding professionals’ views of DOOH advertising is important for anyone considering this promising marketing communication platform. Using qualitative interviews with 18 practitioners, this study discovered six themes concerning DOOH advertising in South Africa: its development, barriers, the share of DOOH advertising in various environments, the quality and quantity of exposure, and point-of-transit, point-of-purchase and point-of-wait DOOH advertising. The findings were used to highlight some focus areas for practitioners to develop and overcome obstacles in the South African DOOH advertising landscape. This study is the first of its kind on DOOH advertising and helps to fill a gap in the existing literature on out-of-home advertising and advertising practitioners’ research in an emerging market.